PERANCANGAN DAN REALISASI E-LOCK SYSTEM MENGGUNAKAN JARINGAN GSM - Febrian Hadiatna; Ratna Susana (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2017)
Abstract In this study has been designed an electronic security system for the door (E-Lock System). This system uses the GSM network to send access commands through short messages service (SMS). This system uses SMS, because many people have been using SMS for communication since last 10 years. The system hardware uses ATMega16 as microcontroller and wavecom module as GSM modem to transmit or receive SMS data. Passwords is used on this system to access electronic key through SMS. People who only has room access permissions can use it. Not only can access the door, E-Lock System has ability to display the history of the user access the door and able to detect human objects in the room. Object detection process is done by PIR sensor which has been integrated with this system. Many of the testing processes performed on this system, such as hardware testing, data transmission testing and integrated system testing. Test results have shown that every menu on the system can be accessed through SMS by the user. The maximum data can be displayed from history menu is limited, only the last 8 users.